Mamíferos continentales del Mioceno tardío a la actualidad en la Argentina: cincuenta años de estudios - Vucetich, María Guiomar (2007)
Ameghiniana was created 50 years ago. During this lapse, the late Cenozoic paleomastozoology developed exponentially in Argentina. Many of the papers dealed with systematics. However, fossil mammals were also used for establish the chronological scale based on a biostratigraphic sequence of faunas mainly from the Pampean area. This scale proved valid for other South American areas. Besides, mammals were used as proxies for understanding the continental climatic evolution and, at the same time, biogeographic studies flourished. In recent years, many paleoecological and morphofunctional studies were carried out. Certainly, the last 50 years were the most productive time in Argentina since the pioneering work of Florentino Ameghino.